Improvements in Clinical Durability From Functional Biomimetic Metallic Dental Implants - Al-Zubaidi, Saad M.; Madfa, Ahmed A.; Mufadhal, Abdulbaset A.; Aldawla, Mohammed A.; Hameed, Osan S.; Yue, Xiao-Guang (Frontiers in Materials, 2020)
The goal modern dentistry is to restore the patient to normal function, speech, health and esthetics, regardless to the atrophy, disease, or injury of the stomatognathic system. Dental implants provide a foreseeable treatment choice for partial and complete edentulism through the placement of a fixed permanent artificial root to support prosthetic dental crowns. Even though the high survival rates, long-term dental implant failures are still reported, leading to implant removals and additional financial and health burdens. These failures are due to poor implant integration, mechanical instability, inflammation, necrosis and infections, and related lengthy patient care, pain and loss of function. Therefore, the objective of the current publication is to find out major representatives of implants along with the current and emerging strategies and technologies for surface and bulk modification used to improve biological and mechanical performance under function. Notable research is highlighted the current developments of biologically active dental implant surfaces and their effect on osseointegration. In addition, dental implant based on functionally graded concept inspired by the human bone is reviewed.